Jacked Box Versus Cut and Cover Technique for the Pedestrian Underpass Construction in Brisbane - A Purwodihardjo (The Australasian Institute of Mining and Metallurgy, 2011)
Evaluation of the construction method used for the pedestrian underpass construction at Ipswich Road, Brisbane, Australia is presented in this paper. The pedestrian underpass was constructed through the existing railway embankment between Harrogate and O’Keefe Streets on the eastern side of Ipswich Road. This underpass construction is part of the CLEM7 tunnel project (formerly known as the North-South Bypass Tunnel) which is the longest toll road in Australia at a total length of 6.8 km. The jacked box construction technique was initially identified as a preferred option during the tender and concept design phases. However at the final design stage, the cut and cover technique was selected as this method can reduce the construction time and cost significantly. The design and construction teams effectively managed the challenges, complexities and risks associated with undertaking cut and cover tunnel through the existing heavily utilised rail embankment. The on-site construction time for the underpass using the cut and cover technique was reduced to less than 42 hours.